IMPLEMENTASI JAMINAN KESEHATAN DAERAH: STUDI KASUS DI KABUPATEN SLEMAN - Sukarno Sukarno; Ani Nurhayati (NATAPRAJA, 2017)
The purpose of this article was to know the implementation of regional health insurance. This research is empirical juridical research. This research was conducted with field research aimed at the implementation of regional health insurance after the enactment of Sleman Regent Regulation No. 60 of 2012. The results of this research indicated that the implementation of regional health insurance after the enactment of Sleman Regent Regulation No. 60 of 2012 follow: Regional Health Insurance Program in Sleman District has a goal to provide quality and affordable services to the community, maximizing health financing for the Sleman Slum community. Each JAMKESDA participant had the right to receive basic health services including outpatient and inpatient services, as well as Advanced Advanced Outpatient Health Care (RJTL), Advanced Inpatient (RITL), delivery and emergency care services. Constraints faced include limited local budgets for regional financing and inadequate health facilities and resources. In addition, other obstacles related to procedural administrative, constraints derived from data collection, constraints that are socio cultural and human resource constraints (HR). Keywords: Implementation, Health Insurance, Regional.